Distribution and morphological abnormalities of recent foraminifera in the Marano and Grado Lagoon (North Adriatic Sea, Italy) - MELIS, R.; COVELLI, S. (Mediterranean Marine Science, 2013)
The Marano and Grado Lagoon, is a northern Adriatic wetland system of relevant naturalistic and economic value, that is constantly under quality control in accordance with the current environmental directives. Benthic foraminifers community with its morphological abnormalities were investigated in the recent sediments (about 10 years old) of 21 stations collected in the framework of the “MIRACLE” Project which aimed at testing the coexistence of clam farming with high Hg contamination. Euryhaline foraminifers, well known in Mediterranean brackish-waters, mainly characterizes the total assemblage. A. tepida dominates in areas characterized by low salinity, high clay and Corg content, but also to anthropogenic pressure. E. gunteri and H. germanica are recorded in the western sector of the lagoon, which is more affected by salinity variations and agricultural activities. Slightly higher values of assemblage diversity appear in less restricted areas of the lagoon or, at least, where physical parameters such as temperature and salinity are less variable. The test abnormalities, carried out on total assemblage, shows that the FAI (Foraminiferal Abnormality Index) values always exceed 1% of the total assemblage, with clear decreasing gradients from inland to the sea (from N to S) and from W to E in the studied area.